ANALYSIS OF THE PROFIT SHARING SYSTEM IN BMT NU BUSINESS CAPITAL FINANCING PRODUCTS, TLOGOSARI BRANCH, BONDOWOSO REGENCY - Feri Ubaidillah; Mohammad Alief Hidayatullah M.E (SEAN Institute, 2023)
This research aims to analyze the profit sharing system in business capital financing products implemented by BMT Nu Tlogosari branch, Bondowoso Regency. The profit sharing system is a sharia financial principle that prioritizes the fair distribution of profits and risks between financial institutions and financing recipients. This research focuses on identifying the mechanism of the profit sharing system, and determining the ratio in BMT Nu business capital financing products for business actors and communities in the region.The research method used is a qualitative approach with data collection techniques through in-depth interviews with BMT Nu, In conclusion, analysis of the profit sharing system in the business capital financing product of BMT Nu Tlogosari branch, Bondowoso Regency, shows success in implementing sharia principles, encouraging local economic growth, and providing fair and sustainable financial alternatives.